Neuroeducação e ensino das Ciências : contribuições cognitivas para o ensino fundamental I - Batista, Érika da Costa (2018)
The present study deals with Neuroeducation and Science Teaching and the cognitive contributions to Elementary Education I. The Neuroscience applied to Education can be a great allied in the practices of the teachers, because it allows to know the organization and functions of the brain, the cognitive processes, the attention, memory and relationships with emotion, motivation and performance in order to contribute to the student's learning process. The general objective of this research was to analyze the teaching and learning process of Science Teaching, in the fundamental I, in the sense of the study and applicability of the cognitive contributions from the knowledge of Neuroeducation. The research is of the qualitative type based on the phenomenological method. As a methodological procedure, the field research was adopted, the bibliographic support was fundamental to decipher the object being researched and to contribute to the data analysis, after the organization was performed. Notes were used in the field notebook, observations in the classroom and intervals for students' behavior to be perceived, both in the games and in the dialogues about learning; other procedures were the photographic record important methodological support because it instantly recorded the moment of the activity, and holding of workshops for data collection, which were subsequently analyzed through content analysis. The locus of the research was a Public School of the state network of Manaus, being 22 subjects and 3 teachers of the 5th grade of Elementary School I. With this work it was possible: To verify the contributions of Neuroeducation, specifically regarding the understanding of the learning process in the Science Teaching; To verify the perception of the students of the 5th grade of Elementary School of a school of the state public network of Manaus concerning the Teaching of Sciences, based on the contributions of Neuroscience to the educational processes; To evaluate the results obtained using the necessary knowledge regarding Neuroeducation that can subsidize and contribute to the educational process of learning in Science Teaching. Keywords: Neuroeducation; Neuroscience; Education; Science Teaching.